RANCANG BANGUN SISTEM MONITORING DAN KONTROL BUDIDAYA JAMUR TIRAM BERBASIS INTERNET OF THINGS (IoT) - Suthami Ariessaputra; Indra Sastra; Sudi Mariyanto Al Sasongko (Depertment of Electrical Engineering University of Mataram, 2023)
Technology in agriculture continues to develop along with human needs. IoT technology has also been applied in agriculture, including oyster mushroom cultivation. Mushroom cultivation must pay attention to several aspects, among others: environment, temperature, and humidity during the maintenance period. The temperature in the barn must be maintained in the range of 25°C-30°C. The optimum air humidity required is between 70%RH and 90%RH. Mushroom farmers usually use existing experience in cultivating and developing oyster mushrooms. Changes in the barn can change suddenly, so it is necessary to observe the environmental conditions of the mushrooms regularly so that the mushrooms can develop optimally. So, it is necessary to build a system that can control humidity and temperature in mushroom cultivation. The system uses IoT-based technology to monitor the temperature and humidity in the mushroom-growing media with certainty so that mushroom growth becomes more optimal. The monitoring and temperature control system in oyster mushroom cultivation can run well while maintaining the temperature at 27.9% and humidity at 90.10% and can be displayed on the LCD Display.